EFFECT OF STRUCTURAL PARAMETERS OF BRIJ SURFACTANTS ON SELF-EMULSIFICATION OF POORLY SOLUBLE DRUG - CHOUHAN, SHAILENDRA; CHAUHAN, LALIT SINGH; KHAMBETE, HEMANT (International Journal of Applied Pharmaceutics, 2024)
Objective: The objective of the present investigation was to optimize the excipient concentration, that is of oil, surfactant and co-surfactants to form a Self Emulsifying Drug Delivery Systems (SEDDS) using best possible combination of excipients. The present study aims to investigate the effect of homologous Brij surfactant on the self-emulsification of aceclofenac. Methods: Three Brij surfactants Brij-35, Brij-58 and Brij-98 were selected for the study along with a common co-surfactant ethanol. The lipid carrier used was almond oil. The combinations of surfactants with ethanol were subjected to a pseudoternary diagram study. Results: The best combination after the pseudoternary diagram study was found to be of Brij-58 and ethanol. The reason may be the difference in chains of Brij-35, Brij-58, Brij-98. The double bond of Brij-98 chain makes it rigid, whereas absence of unsaturation in Brij-58 imparts flexibility to its chain, leading to better shielding of the hydrophobic compartment when used along with ethanol. The Brij-35 chain consist of 12 carbons and Brij-58 chain consists of 16 carbons so latter offers larger core for drug solubilization. Simplex lattice design was used for optimization. Seven formulations were developed using almond oil, Brij-58, ethanol and evaluated. Formulation F2 was found to be best amongst all with globule size of 182 nm and zeta potential of-19.73 mV, indicating formation of stable microemulsion. Conclusion: The surfactant possessing large and flexible chains along with less number of polyoxyethylene groups offers greater space for drug solubilization and better protection of the hydrophobic core and lead to finer microemulsification.